Optimization of Growth Conditions for Production of Organophosphorous Phosphatase Enzymes in Three Bacteria Species Isolated from Dairy Farms in Kenya - Juma Tom, Felix; Kamau Gicharu, Gibson; Gona Makenzi, Nzaro; Mwagandi Chimbevo, Lenny; Mwamburi Mjomba, Fredrick; Juma Amana, Mzee; Atego Norbert, Adum; Lydia Haro, Anzazi (Multidisciplinary Journal of Technical University of Mombasa, 2024)
Chlorfenvinphos is one of the organophosphates largely produced around the world to control mites and ticks in dairy farming. However, it is toxic and has serious effects on the nervous system and other organ systems. It has a long residual effect in the environment posing risks to both aquatic and terrestrial ecosystems.  In this study, three species of bacteria isolated from chlorpyrifos contaminated dairy farms in Kenya were screened for their ability to produce chlorfenvinphos degrading organophosphorus phosphatase enzymes. The isolates, Advenella kashmirensis, Micrococcus luteus, and Lysinibacillus sphaericus grew at different rates when both temperature and pH were varied. The optimal growth temperature for the three isolates was 35°C while the optimal pH of M. luteus and L. sphaericus was 7 and 6 for A. kashmirensis. At these optimal conditions, A. kashmirensis had the highest growth (OD 0.175) followed by L. sphaericus (OD 0.132) while M. luteus had the lowest (OD 0.106). Crude protein concentration was highest for A. kashmirensis (465.4 ± 31.8 μg/mL) and was significantly different from the concentrations of the other isolates (p < 0.05). This suggests its suitability for applications requiring high concentrations of total proteins.  On purification of crude protein using ammonium sulfate precipitation and gel filtration, A. kashmirensis exhibited the highest enzyme activity (19.8 ± 0.8 µMol/Min and was significantly different from M. luteus (13.8 ± 0.98 µMol/Min and L. sphaericus (11.8 ± 0.2 µMol/Min. These results suggest A. kashmirensis is superior in bioremediating chlorfenvinphos polluted environments and can be used to clean up polluted dairy farms. However, more studies are required to explore how the isolates interact with each other in their natural environments with a view of coming up with more efficient degradation process to restore polluted dairy farms and reduce the risk of the acaricide entering aquatic and terrestrial ecosystems from where it can easily enter into food chains affecting a wide variety of organisms.
Keywords: Chlorfenvinphos; Organophosphates; Bioremediation; Organophosphorus Phosphatase Enzymes